Mechanism of UV-assisted TiO2/reduced graphene oxide composites with variable photodegradation of methyl orange. Issue 89 (27th September 2015) - Lu, Zeyu; Chen, Guochang; Hao, Wenbin; Sun, Guoxing; Li, Zongjin
<x xml:space="preserve">Abstract</x> TiO2/reduced graphene oxide (TiO2/rGO) composites were synthesized by ultraviolet irradiation method, and the mechanism of TiO2/rGO composites with variable photodegradation efficiency of methyl orange was proposed.